Retrospective analysis of changes in response topographies of escape‐maintained aggressive behavior during functional analyses. Issue 3 (13th May 2018) - Hernández, Varsovia; Fernand, Jonathan K.; Vollmer, Timothy R.; Slocum, Sarah K.
Abstract : We observed changes in the rates of response topographies during the demand condition of functional analyses for participants who demonstrated problem behavior maintained by escape. Over the course of the functional analysis for each participant, the number of topographies decreased from the first to the last session. Additionally, after the first session of the demand condition the rate of responding for one topography increased or remained at high levels while the rates of all other topographies decreased. The implications of these results when conducting functional analysis are discussed.